ARAH KEBIJAKAN PRASARANA TRANSPORTASI DI WILAYAH JAWA TIMUR BERDASARKAN PERSEPSI PEMANGKU KEPENTINGAN - Wicaksono, Achmad; Wahyudi, Wahid; Mulyono, Agus Taufik (Jurnal Transportasi, 2014)
Transport infrastructure in East Java today has grown well, it has been proven from the significance effect to the economic growth of East Java Province. Therefore, it is necessary to assess the condition of existing transportation infrastructure currently in the region of East Java Province, and identify itâs weaknesses to be improved in the future. This study aims to identify problems and potential policy directions of transport infrastructure in the province of East Java in the future, particularly the priority of aspects to be improved. This study was conducted with a Focus Group Discussion (FGD), which has been used a questionnaire-based method called as IPA (Important Performance Analysis), with respondents are officers in the East Java Provincial Transport Department and representatives from the City and Regency Department of Transportation in the Province of East Java. The performance aspect that related with passenger which is identified to be improved are (a) integration aspects and (b) the capacity of the passenger activity. Related performance of freight transport that need to be improved are aspects: (a) integration of multi-modal services, (b) the regularity of the service, (c) ease accesses, (d) timeliness, (e) order, and (f) efficiency. Â Keywords: transport policy, transport infrastructure, passengers and goods transportÂ Â Prasarana transportasi di Jawa Timur saat ini telah berkembang cukup baik, terbukti peranannya semakin terlihat dari signifikasi pertumbuhan ekonomi di Provinsi Jawa Timur. Oleh karena itu perlu dilakukan kegiatan untuk menilai kondisi prasarana transportasi yang ada saat ini di wilayah Provinsi Jawa Timur dan mengidentifikasi kelemahannya guna memperbaiki kondisi di masa mendatang. Penelitian ini bertujuan untuk mengidentifikasi masalah dan potensi arah kebijakan prasarana transportasi di Provinsi Jawa Timur di masa mendatang, khususnya terkait dengan prioritas aspek sasarannya. Penelitian ini dilakukan dengan Â Focus Group Discussion menggunakan kuesioner berbasis metode Important Performance Analysisdan responden adalah semua pejabat di Dinas Perhubungan Provinsi Jawa Timur dan perwakilan dari Dinas Perhubungan Kabupaten/Kota sewilayah Provinsi Jawa Timur. Kinerja terkait angkutan penumpang yang teridentifikasi perlu untuk ditingkatkan adalah (a) aspek keterpaduan dan (b) daya tampung untuk aktivitas penumpang. Kinerja terkait angkutan barang yang teridentifikasi perlu untuk ditingkatkan adalah aspek-aspek: (a) keterpaduan layanan multi moda, (b) keteraturan layanan, (c) kemudahan dicapai, (d) ketepatan waktu, (e) ketertiban, dan (f) efisiensi.Â Kata-kata kunci: kebijakan transportasi, prasarana transportasi, angkutan penumpang dan barang